Strategi NGO Lingkungan Dalam Menangani Polusi Udara di Jakarta (Greenpeace Indonesia) - Fariz Ruhiat; Dudy Heryadi; Akim - (Andalas Journal of International Studies (AJIS), 2019)
Air pollution is one of the global problems being faced by most major cities in the world. As the problem of air pollution increases, non-state actors emerge because of the limited role of the state in tackling these environmental problems. One of the non-state actors who is concerned about the problem of air pollution is Greenpeace which is a form of international non-governmental organizations. This study aims to describe an understanding of environmental NGO strategies in overcoming air pollution in Jakarta. The researcher uses qualitative research methods with a literature study approach. In library studies, data and information are collected and analyzed to understand the phenomenon under review. Based on the results of discussion and data analysis, Greenpeace has implemented its strategy in overcoming air pollution in Jakarta. From the nine strategies described by McCormick, Greenpeace has a tendency to use undertaking research strategies and Campaigning & organizing public protest